PENGARUH PENGGUNAAN DAUN SIRIH HIJAU (PIPPER BETLLE LIN) PADA WANITA USIA SUBUR DENGAN KEPUTIHAN (LEUKHOREA) - Wahida Wahyuni Siahaan; Prasida Yunita; Dian Juni Ekasari; Nova Roza (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Humid weather encourages the growth of fungi, many Indonesian women suffer from reproductive diseases, including vaginal discharge (leukorrhea). A woman's reproductive system can be negatively affected by chronic vaginal discharge. Avoiding pharmaceutical treatments for vaginal discharge (leukorrhea) can be done with the help of green betel leaves (pipper betlle lin). Women of childbearing age at PMB Bdn. Atlantika, S. Keb Batam City will participate in this study to find out how the use of green betel leaves (pipper betlle lin) affects vaginal discharge (leukorrhea). A quantitative single-group pre-test-post-test study was used. There were a total of 25 participants in this study. Accidental Sampling was the method used for sampling. The Wilcoxon test was used for statistical testing... This study found that after treating water with boiled green betel leaves (pipper betlle lin), the average value increased from 1.021 to 332. Based on the results of this study (p-value 0.000 <0.5), it can be concluded that giving boiled green betel leaves (pipper betlle lin) to mothers at PMB Bdn. Atlantika, S.Keb Batam City, has the effect of reducing vaginal discharge (leukorrhea). With a p-value of 0.000 <0.05, it can be concluded that the use of green betel leaves (pipper betlle lin) has an effect on pathological vaginal discharge (leukorrhea) in women of childbearing age at PMB Bdn. Atlantika, S.Keb